2007
DOI: 10.1097/wnr.0b013e3282742115
|View full text |Cite
|
Sign up to set email alerts
|

Citalopram modulation of neuronal responses to aversive face emotions: a functional MRI study

Abstract: This study investigated the serotonergic modulation of face emotion processing using blood oxygen level-dependent (BOLD) functional MRI. In a placebo-controlled, balanced order design, intravenous citalopram (7.5 mg) was given to 12 male volunteers 60 min before a covert face emotion recognition task. Angry, disgusted and fearful faces produced BOLD signal responses, which were broadly consistent with previous findings. Citalopram enhanced the BOLD signal response in the left posterior insula (together with no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
97
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(111 citation statements)
references
References 21 publications
12
97
1
1
Order By: Relevance
“…This concurs with some studies in human subjects that found acute 5-HT manipulations selectively to affect reactions to negative stimuli (Browning et al, 2007;Chamberlain et al, 2006), punishment prediction (Cools et al, 2008b), and the activation of brain areas involved in error detection and processing of aversive events (Anderson et al, 2007;Del-Ben et al, 2005;Evers et al, 2005;McKie et al, 2005).…”
Section: Discussionsupporting
confidence: 73%
“…This concurs with some studies in human subjects that found acute 5-HT manipulations selectively to affect reactions to negative stimuli (Browning et al, 2007;Chamberlain et al, 2006), punishment prediction (Cools et al, 2008b), and the activation of brain areas involved in error detection and processing of aversive events (Anderson et al, 2007;Del-Ben et al, 2005;Evers et al, 2005;McKie et al, 2005).…”
Section: Discussionsupporting
confidence: 73%
“…Contrary to our expectations, here we did not find evidence that citalopram decreases amygdala activation in IED. Moreover, although the results in controls (escitalopram increases amygdala activation) are in line with a prior report (Bigos et al, 2008), some studies did not observe an effect of citalopram on amygdala activity (Brühl et al, 2010;Henry et al, 2013) and several other single-dose and short-term citalopram administration studies found amygdala decreases (Del-Ben et al, 2005;Harmer et al, 2006;Anderson et al, 2007;Arce et al, 2008;Murphy et al, 2009;Windischberger et al, 2010). Although it is possible that our results in controls are perhaps due to sampling error (see Limitations section), several other methodological issues in citalopram administration studies also need to be considered.…”
Section: Discussionsupporting
confidence: 70%
“…Research has mostly shown that, in controls, a single-dose or short-term administration of citalopram reduces amygdala activity (Del-Ben et al, 2005;Harmer et al, 2006;Anderson et al, 2007;Murphy et al, 2009;Windischberger et al, 2010), although increases have also been found (Bigos et al, 2008). We hypothesize that escitalopram will lower amygdala activity in IED.…”
Section: Introductionmentioning
confidence: 98%
“…Thalamocortical coupling is altered in depression and antidepressant therapy targets this connection [26][27][28]. HC healthy control subjects, rMD remitted depressed subjects, aMD acute depressed patients fMRI-1 functional magnetic resonance imaging session one, HAM-D 24 Hamilton Depression Rrating Scale (24 item version), HAM-A Hamilton Anxiety Rating Scale, BDI Beck Depression Index, CGI Clinical Global Impression scale, f female, m male, y years, m months, r right, l left a p-value chi-square test b p-value analysis of variance c p-value t-test d for detiailed medication see supplementary Table S5 e only one patient Antidepressant effects on the pulvinar and the thalamus are substantiated in other fMRI tasks [29][30][31]. Moreover, thalamocortical connectivity was altered upon ketamine administration [32] and transracial magnetic stimulation to the dorsolateral prefrontal cortex elevated activity in the pulvinar nuclei [33].…”
Section: Discussionmentioning
confidence: 99%